2021
DOI: 10.1111/ppl.13363
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Iron Transporter (Like) proteins: Regulators of cellular iron accumulation in plants

Abstract: Iron is not only important for plant physiology, but also a very important micronutrient in human diets. The vacuole is the main site for accumulation of excess amounts of various nutrients and toxic substances in plant cells. During the past decade, many Vacuolar Iron Transporter (VIT) and VIT‐Like (VTL) genes have been identified and shown to play important roles in iron homeostasis in different plants. Furthermore, recent reports identified novel roles of these transporter genes in symbiotic nitrogen fixati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…In addition, expressions of key enzymes in NA and DAM synthesis pathways, such as SAM, NAS, NAAT, and DMAS, were signi cantly up-regulated (Figure S3D, I, G, F), which was consistent with previous results in wheat [38][39][40] and rice [33][34][35]. Previous studies have shown that the expression abundance of genes related to Fe uptake and transport in mitochondria [41,42], chloroplasts [43,44], and vacuoles [45] are signi cantly up-regulated under Fe-de ciency stress. This conclusion was consistent with our transcriptome results (10H-R).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, expressions of key enzymes in NA and DAM synthesis pathways, such as SAM, NAS, NAAT, and DMAS, were signi cantly up-regulated (Figure S3D, I, G, F), which was consistent with previous results in wheat [38][39][40] and rice [33][34][35]. Previous studies have shown that the expression abundance of genes related to Fe uptake and transport in mitochondria [41,42], chloroplasts [43,44], and vacuoles [45] are signi cantly up-regulated under Fe-de ciency stress. This conclusion was consistent with our transcriptome results (10H-R).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that when AtVTL1, AtVTL2, or AtVTL5 is expressed under the 35S promoter in the background of nramp3/nramp4 or vit1-1, in the two mutants [46], AtVTL1, AtVTL2 or AtVTL5 can restore root growth. In yeast, the VIT homologous Ca 2+ -Sensitive-Cross-Complementer (CCC1) protein is a vacuolar Fe transporter that transports Fe to the vacuole under condition of excess Fe [45]. The pastatin promoter is used on cassava for overexpansion, and the expression of atvit1 gene is positively correlated with the increase of Fe concentration in storage roots.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of key enzymes in the NA and DAM synthesis pathways, such as SAM , NAS , NAAT , and DMAS , was significantly upregulated (Figure S 4 D, I, G, F), which was consistent with previous results reported in wheat [ 38 40 ] and rice [ 33 35 ]. Previous studies have shown that the expression levels of genes related to Fe uptake and transport in mitochondria [ 41 , 42 ], chloroplasts [ 43 , 44 ], and vacuoles [ 45 ] are significantly upregulated under Fe-deficiency stress. This conclusion was consistent with our transcriptomic results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that when AtVTL1 , AtVTL2 , or AtVTL5 is expressed under the 35S promoter in the background of two mutants of nramp3 / nramp4 or vit1-1 [ 46 ], AtVTL1 , AtVTL2 or AtVTL5 can restore root growth. In yeast, the VIT homologous Ca 2+ -Sensitive-Cross-Complementer (CCC1) protein is a vacuolar Fe transporter that transports Fe to the vacuole under conditions of excess Fe [ 45 ]. The pastatin promoter was used for overexpression in cassava, and the expression of the AtVTL1 gene was positively correlated with the increase in Fe concentrations in storage roots.…”
Section: Discussionmentioning
confidence: 99%
“…The Arabidopsis VIT is highly expressed in developing seeds and localizes at the vacuolar membrane (Kim et al, 2006). The rice genome contains two VIT and five VTL genes (Ram, Sardar, et al 2021). OsVIT1 and OsVIT2 mediate the transport of iron, manganese, and zinc into the vacuole and confers heavy metal homeostasis in rice plants.…”
Section: Heavy Metal Uptake and Transport Mechanisms In Ricementioning
confidence: 99%